Biblioteki naukowe w procesie transformacji - Michniewicz-Wanik, Krystyna (Archiwa, Biblioteki i Muzea Kościelne, 2016)
Storing the produced knowledge and managing it with the use of new technologies is a big challenge for libraries. The transformation of research libraries, as a continuous adaptation of services to the changing needs of users, requires, apart from modern IT tools, the reconstruction of the organizational culture. The theory of the organization (the method of change management) indicates the important role of leaders, who should have a vision of the future of libraries, taking account of how higher education functions as a whole and the ability to positively influence the staff while achieving new goals.